2019
DOI: 10.18517/ijaseit.9.1.5322
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Plant Disease Visual Symptom Detection in Digital Images Based on Superpixels

Abstract: Quantifying diseased areas in plant leaves is an important procedure in agriculture, as it contributes to crop monitoring and decision-making for crop protection. It is, however, a time-consuming and very subjective manual procedure whose automation is, therefore, highly expected. This work proposes a new method for the automatic segmentation of diseased leaf areas. The method used the Simple Linear Iterative Clustering (SLIC) algorithm to group similar-color pixels together into regions called superpixels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The developed approach seems an efficient tool to detect the disease using the Spectral Disease Index (SDI). Salazar-Reque et al [12] have proposed a novel crop protection method in the agriculture industry. It is, however, a time-consuming and very subjective procedure, which automation is therefore highly anticipated.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed approach seems an efficient tool to detect the disease using the Spectral Disease Index (SDI). Salazar-Reque et al [12] have proposed a novel crop protection method in the agriculture industry. It is, however, a time-consuming and very subjective procedure, which automation is therefore highly anticipated.…”
Section: Related Workmentioning
confidence: 99%
“…To achieve only the desired features from the whole leaf image, we will apply SURF as a feature extraction technique on the ROI of leaf image [12]. This technique extracts only those parts of the leaf, which is affected by the disease.…”
Section: Feature Extraction Form Leaf Roimentioning
confidence: 99%
“…In [7], the authors demonstrated a framework for classifying images of using gradient-based features. In another work [8], Simple Iterative Linear Clustering Algorithm (SLIC) method is used group the color features (super pixels) which in turn are used to train the ANN to classify whether the super pixels that are neither healthy nor healthy. In [9], the authors recommended better method for diagnosing apple leaf diseases using Deep Neural Network (DNN).…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, color imaging is inexpensive and is easy to handle. Color imaging can capture the color and texture information of an object, and has been implemented to detect and assess plant diseases [18][19][20]. For Fusarium or FHB detection, researchers have explored the usefulness of color imaging.…”
Section: Introductionmentioning
confidence: 99%